2007
DOI: 10.1038/sj.bjc.6603630
|View full text |Cite
|
Sign up to set email alerts
|

The collagenase-1 (MMP-1) gene promoter polymorphism - 1607/2G is associated with favourable prognosis in patients with colorectal cancer

Abstract: Matrix metalloproteinase (MMP) overexpression has been implicated in the pathogenesis of colorectal carcinoma (CRC). Accumulating evidence suggests that MMP promoter single nucleotide polymorphisms (SNPs) effecting gene transcription are associated with enhanced susceptibility for the development of malignant disease, increased tumour invasiveness and poor patient survival. The aim of the current investigation was to determine whether such associations exist in a large CRC patient/control study population. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 57 publications
1
43
3
1
Order By: Relevance
“…These findings were not supported by Hettiaratchi et al [96] , Elander et al [90] and Ohtani et al [103] , who found no influence of the MMP-2 genotype on the colorectal cancer risk (Figure 2). Difference in ethnicity (Australian vs European vs Japanese) or sample size might be the underlying cause of this discrepancy.…”
Section: Colorectal Cancercontrasting
confidence: 55%
See 3 more Smart Citations
“…These findings were not supported by Hettiaratchi et al [96] , Elander et al [90] and Ohtani et al [103] , who found no influence of the MMP-2 genotype on the colorectal cancer risk (Figure 2). Difference in ethnicity (Australian vs European vs Japanese) or sample size might be the underlying cause of this discrepancy.…”
Section: Colorectal Cancercontrasting
confidence: 55%
“…Two meta analyses, both including the study of Xu et al, showed no association between the MMP2 1306 C/T poly morphism and colorectal cancer susceptibility [87,100] . Xu et al [104] also reported that patients with the CC genotype had more frequent serosa/adventitia involvement, while none of the other studies described any correlation with clinicopathological parameters or survival, except for the study of Langers et al, where the TT genotype was shown to be an indicator of poor 10year survival [8993,96,97,99,103,105] . In the Xu et al [104] cohort of 126 CRC patients and 126 control patients, two other polymorphisms of MMP2 (790 T/G, 955 A/C) were not associated with cancer susceptibility or infiltration depth, while GG genotype carriers of the MMP2 1575 G/A polymorphism had an increased risk of developing CRC and more frequent serosa or adventitia invasion compared to the other geno types, similar to that with the 1306 CC genotype [102] .…”
Section: Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, when the Caucasian patients were subtracted from the ethnically mixed group, and the latter analyzed, there was no association between the T allele and node status when corrected for grade (P = 0.96; odds ratio, 1.05; 95% CI, 0.18-5.93). Similarly, in colorectal cancer, whereas a relationship between the MMP-1 2G/2G genotype and poor prognosis has been identified in an Italian cohort of patients with colorectal cancer (30), no such relationship was identified in a recent large Australian study (31).…”
Section: Discussionmentioning
confidence: 99%